Design and sizing eVTOL aircraft (flight physics and flight simulation) - Lim, Shi Jie (Nanyang Technological University, 2022)
The usage of eVTOL (Electric Vertical Take-Off and Landing) aircraft as air taxis for Urban Air Mobility (UAM) has seen a rising trend in recent years. As more companies set out to launch new demonstrators to revolutionise air transport, an underlying problem lies in the design and testing process which heavily utilizes resources such as manpower, time and money for the Research and Development of innovative eVTOLs. The report strives to explore various framework and modelling tools used in the industry to develop a flight simulator, in hopes of alleviating the costs incurred during the design and testing phase. Studies were done to learn the steps required to develop a flight simulator, following which, explore the flight physics of two flight models, hover mode and cruise mode. The goal was to unify both models into one which would work for both phases of flight, known as the transition model. The prototype designed by the eVTOL Research and Innovation team was built and flown, before comparing the performance in the developed simulator. Studies were then done on transitional flight, PID tuning and One Engine Inoperative (OEI) situations.